SURGICAL TREATMENT OF VESICOVAGINAL FISTULA; AN AUDIT OF 69 CASES - Haq, Amin ul; Jan, Mir Alam; Alam, Muhammad; Ghani, Azra (Journal of Postgraduate Medical Institute, 2012)
Objective: The aim of this study is to assess the outcome of patients undergoing repair of vesicovaginalfistula.Methodology: This descriptive study which was conducted from May 2002 to March 2008 the Departmentof Urology Lady Reading Hospital Peshawar. A total of 69 patients with Vesicovaginal fistula wereincluded in this study. A detailed history and physical examination with special emphasis on previousgynecological and obstetrical events was recorded. All these patients underwent routine investigations likeHB%, CBC, Urianalysis, renal function test and viral profile with ultrasonography of the abdomen &pelvis. Intravenous Urography(IVU) was offered to those patients who had upper tract dilatation onultrasonography. Preliminary cystoscopy and Vaginoscopy was performed in all patients to diagnose VVFand plan the surgical approach.Result: The mean age was 39.07(+10.031)years. Thirt eight (55%) patients developed fistula due toobstetrical reasons while 30 (43-47%) had gynaecological surgeries and only one patient developed fistulaafter radiotherapy. The average size of the fistula was 3.36 cm: Transabdominal repair of fistula was donein 58(84.1%) patients while 11(15.9%) has transvaginal repair. Successful repair was achieved in65(93.7%) patients.Conclusion: Vesicovaginal fistula can be successfully managed surgically. Proper preoperative assessmentof the patients is mandatory for selection of the surgical approach.